Breast cancer patient-derived explant cultures recapitulate in vivo drug responses - Pettersen, Solveig; Øy, Geir Frode; Egeland, Eivind Valen; Juell, Siri; Engebråten, Olav; Mælandsmo, Gunhild Mari; Prasmickaite, Lina (Frontiers in Oncology, 2023)
Assessment of drug sensitivity in tumor tissue ex vivo may significantly contribute to functional diagnostics to guide personalized treatment of cancer. Tumor organoid- and explant-cultures have become attractive tools towards this goal, although culturing conditions for breast cancer (BC) tissue have been among the most challenging to develop. Validation of possibilities to detect concordant responses in individual tumors and their respective cultures ex vivo is still needed. Here we employed BC patient-derived xenografts (PDXs) with distinct drug sensitivity, to evaluate different conditions for tissue dissociation, culturing and monitoring of treatment efficacy ex vivo, aiming to recapitulate the in vivo drug responses. The common challenge of discriminating between tumor and normal cells in the cultured tissue was also addressed. Following conventional enzymatic dissociation of BC tissue, the tumor cells stayed within the non-disrupted tissue fragments, while the single cells represented mostly normal host cells. By culturing such fragments as explants, viable tumor tissue could be maintained and treated ex vivo, providing representative indications on efficacy of the tested treatment. Thus, drug sensitivity profiles, including acquired chemoresistance seen in the PDXs, were recapitulated in the respective explants. To detect the concordant responses, however, the effect monitoring had to be harmonized with the characteristics of the cultured tissue. In conclusion, we present the feasibility of BC explants ex vivo to capture differences in drug sensitivity of individual tumors. The established protocols will aid in setting up an analogous platform for BC patient biopsies with the aim to facilitate functional precision medicine.